Pengaruh Persepsi Harga, Kualitas Pelayanan Dan Kualitas Produk Elektronik Terhadap Minat Beli di PT Benka Solusi Mandiri Kota Bekasi Provinsi Jawa Barat - Rizky Pratama Jundawa; Ida Bagus Cempena (Nirta Learning Centre, 2025)
Along with the rapid development of the business world, especially the service sector, it has become one of the industries that continues to grow, especially in Bekasi. This has encouraged the emergence of various innovations in doing business in the service sector to attract consumer attention. One of them is PT. Benka Solusi Mandiri Bekasi City. However, in the midst of increasingly tight competition, Pt. Benka Solusi Mandiri needs to understand the factors that influence consumer Purchase Interest, such as Price Perception, Service Quality, and Product Quality to continue to develop strategies in order to increase customer Purchase Interest. This study is a quantitative study with the aim of testing and analyzing the effect of Price Perception, Service Quality, and Product Quality on Electronic Purchase Interest at PT. Benka Solusi Mandiri Kota Bekasi. With a sample of 100 respondents collected using a questionnaire, the data analysis techniques used include Descriptive Test, Instrument Test, Classical Assumption Test, and Hypothesis Test using SPSS software. This research was conducted in February - March 2025. The results of this study indicate that Price Perception partially has a significant effect on Purchase Intention, Service Quality partially has a significant effect on Purchase Intention, and Product Quality partially has a significant effect on Purchase Intention. Simultaneously, Price Perception, Service Quality, and Product Quality have a significant effect on Purchase Intention of Electronics at PT. Benka Solusi Mandiri Bekasi City.